“I don’t want to be a burden on others”: Perspectives of "Young-old" Thai Women on Self-reliance, Wellness, and Aging - Nitiwarangkul, Kullanit (Atlantis)

(untitled) (Mount Saint Vincent University, 2026)
This article examines the perspectives of middle- and upper-class “young-old” women (aged 60 to 69) in Thailand on “wellness” amidst the country’s rapidly aging population. Drawing upon findings from my interviews with sixteen older women, it explores how self-reliance has become central to their pursuit of decent physical and mental health. Participants strived to maintain their health, preserve mobility, and reduce dependence on family members. At the same time, some served as caregivers for their families in a culture that emphasizes familial interdependence. Additionally, this paper analyzes how “mental wellness” is framed within self-reliance, shaped by Buddhist teachings and neoliberal ideals, as these women navigate life transitions and sustain their well-being amidst the disruptions of COVID-19. The study further demonstrates their rising concerns and demands for essential resources for their wellness, including health insurance, professional caregiving, and adequate housing, in the absence of sufficient public welfare. The paper offers a nuanced understanding of self-reliance and wellness in later life and promotes interventions to support older individuals. It does so by foregrounding the classed, gendered, and culturally specific experiences of aging women in the Global South, a topic rarely studied in fields such as gerontology and feminist studies.